The Effectiveness of Home-Based Otago Exercise Program Versus Frenkel’s Exercise in Preventing Falls in Elderly Adults: Life Sciences -Physiotherapy - Tep, Abenle; Baruah, Trishna Saikia; Paul, Mantu; Dihidar, Niharika; Dutta, Abhijit (International Journal of Life Science and Pharma Research, 2023)
Fall is the major concern for elderly adults, which can lead to chronic disability and dependency level increases.Impaired muscle strength and instability in balance are the most common causes of falls in older adults. This study aims to findthe effectiveness of a home-based Otago exercise program versus Frenkel's exercise in preventing falls in the elderly. In addition,this study aims to compare the efficacy of a home-based Otago exercise program versus Frenkel's exercise for assessing fall riskand fear of falls. This was a comparative study with thirty subjects who perceived fear of falls, or a history of falls takenconsidering the inclusion criteria, where Group A received Otago exercise (strengthening and balance exercises) and Group Breceived Frenkel's exercise (in supine, sitting and standing positions) with 15 subjects in each group. Timed up and go (TUG) forassessing balance and fall efficacy scale (FES) for determining risk and fear of falls were used as outcome measures. The paired 'ttestwas used to compare both groups' pre and post-intervention results, and the independent 't'-test was used to comparegroups. Group A mean TUG score improved from 16.200 to 11.066, FES 74.733 to 67.866 and Group B's mean TUG score was16.000 to 11.733, FES 75.666 to 69.400. It was found that t = -1.711 is insignificant (p=.098 >0.05). Hence, the home-basedOtago exercise program and Frenkel's exercise were equally effective in improving the balance of the patients. Compared tothe risk and fear of falling, home-based Otago exercise was more effective than Frenkel's.